1998
DOI: 10.1016/s0002-9440(10)65562-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Keratinocyte Growth Factor and Receptor Expression in Human Pancreatic Cancer

Abstract: Keratinocyte growth factor (KGF) is an angiogenic and mitogenic polypeptide that has been implicated in cancer growth and tissue development and repair. Its actions are dependent on its binding to a specific cell-surface KGF receptor (KGFR) , which is encoded by the fibroblast growth factor (FGF) receptor type II (FGFR-2) gene. In the present study , we compared the immunohistochemical localization of KGF and KGFR/ FGFR-2 in the normal and cancerous pancreas using specific antibodies that recognize KGF and KGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 27 publications
4
68
0
2
Order By: Relevance
“…Using immunostaining and in situ hybridization techniques as well as RNase protection assays, we previously reported that FGFR -1, FGFR -2, and the related keratinocyte growth factor receptor (KGFR ) are expressed at relatively high levels in pancreatic cancer cells within the pancreatic tumor mass. 21,22 Using laser capture microdissection and real -time PCR, in the present study we were able to assess the expression levels of all four high -affinity FGFRs in the pancreatic cancer cells from seven different PDAC samples (Fig 9). Three samples exhibited relatively high levels of FGFR -1 ( samples 1, 5, and 6 ), and two of these three samples also exhibited high levels of FGFR -2 and moderate levels of FGFR -3 and -4 (samples 1 and 6 ).…”
Section: Expression Of Fgfrs In Pancreatic Cancer Cells and Tumorsmentioning
confidence: 85%
See 3 more Smart Citations
“…Using immunostaining and in situ hybridization techniques as well as RNase protection assays, we previously reported that FGFR -1, FGFR -2, and the related keratinocyte growth factor receptor (KGFR ) are expressed at relatively high levels in pancreatic cancer cells within the pancreatic tumor mass. 21,22 Using laser capture microdissection and real -time PCR, in the present study we were able to assess the expression levels of all four high -affinity FGFRs in the pancreatic cancer cells from seven different PDAC samples (Fig 9). Three samples exhibited relatively high levels of FGFR -1 ( samples 1, 5, and 6 ), and two of these three samples also exhibited high levels of FGFR -2 and moderate levels of FGFR -3 and -4 (samples 1 and 6 ).…”
Section: Expression Of Fgfrs In Pancreatic Cancer Cells and Tumorsmentioning
confidence: 85%
“…21,22 RNA ( 10 g per sample ) was hybridized overnight at 428C with [ -32 P]CTP -labeled riboprobes, and single-stranded RNA was subsequently digested with RNAse A /T1 according to Ambion's RNase protection assay kit RPA II. Yeast tRNA ( 10 g ) was used as a negative control.…”
Section: Ribonuclease Protection Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In the pancreas, previous works have shown the effect of KGF in ductal-cell proliferation [5]. The expression of this growth factor and its receptors is up-regulated in pancreatic carcinomas [17]. Studies in transgenic mice expressing KGF alone [18] or both KGF and EGF [19] in their beta cells showed that ectopic expression of KGF in the pancreas induces increased ductal-cell proliferation, profound changes in pancreatic morphology and the appearance of hepatocytes within the Fig.…”
Section: Effect Of Kgf On Beta Cell and Ductal Cell Proliferationmentioning
confidence: 99%